2021
DOI: 10.3390/pharmaceutics13040565
|View full text |Cite
|
Sign up to set email alerts
|

Development, Characterization, and Ex Vivo Assessment of Elastic Liposomes for Enhancing the Buccal Delivery of Insulin

Abstract: Buccal drug delivery is a suitable alternative to invasive routes of drug administration. The buccal administration of insulin for the management of diabetes has received substantial attention worldwide. The main aim of this study was to develop and characterize elastic liposomes and assess their permeability across porcine buccal tissues. Sodium-cholate-incorporated elastic liposomes (SC-EL) and sodium-glycodeoxycholate-incorporated elastic liposomes (SGDC-EL) were prepared using the thin-film hydration metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Lyophilization presents a great potential in the pharmaceutical field not only as a technique for the preservation of thermolabile drugs, but also as a technological process for developing drug delivery systems based on nanoparticles. This technique produces oral disintegrating tablets and has been recently applied to produce a mucoadhesive matrix and wafers for buccal drug delivery [ 26 , 27 , 28 ]. The advantages of the sublingual cavity for systemic drug absorption combined with the benefits of liposomes as drug carriers are a promising opportunity for developing innovative pharmaceutical formulations with application to new and old drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Lyophilization presents a great potential in the pharmaceutical field not only as a technique for the preservation of thermolabile drugs, but also as a technological process for developing drug delivery systems based on nanoparticles. This technique produces oral disintegrating tablets and has been recently applied to produce a mucoadhesive matrix and wafers for buccal drug delivery [ 26 , 27 , 28 ]. The advantages of the sublingual cavity for systemic drug absorption combined with the benefits of liposomes as drug carriers are a promising opportunity for developing innovative pharmaceutical formulations with application to new and old drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Ex vivo studies were performed to evaluate the distribution of HIP-nanocomplexes across porcine buccal tissue using a vertical static Franz diffusion cell by using the procedure reported previously. 36 Briefly, the Franz diffusion cell system was set up as described earlier, and 500 µL of FITC-insulin solution, FITC-C1, or FITC-C2 (equivalent to 200 µg/mL FITC–insulin) was loaded into the donor chamber. The studies were directed from the donor to receptor chambers with constant magnetic stirring (600 rpm) at 37°C, and at predetermined time points (0.5, 2, and 4 h), the buccal tissues were washed with PBS buffer (pH 7.4) and dried with soft paper.…”
Section: Methodsmentioning
confidence: 99%
“…Bashyal et al produced sodium cholate-incorporated elastic liposomes and sodium glycodeoxycholate-incorporated elastic liposomes, which were tested across porcine buccal tissues using confocal laser scanning microscopy [ 76 ]. The authors showed significantly enhanced the permeation of insulin with a 4.33-fold increase in the permeability coefficient compared to insulin solution.…”
Section: Applications Of Ultra-deformable Liposomesmentioning
confidence: 99%